Reconnecting to Rebirth a New Progressive Africa and World (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
Prevailing linear theories of historical progress, derived from European experiences, have often obscured Africa's foundational and cyclical contributions to human civilization. This paper critiques this linear paradigm, arguing that it selectively edits history to emphasize a European trajectory from Greece and Rome to the Industrial Revolution while neglecting Africa’s pivotal early roles in human evolution, agriculture, technology, and the early Christian Church. The analysis traces how this external lens, combined with the catastrophic disruptions of the trans-Saharan and trans-Atlantic slave trades, fractured African development. The Atlantic trade, in particular, represented a unique and dehumanizing system that commodified people, triggering internal warfare and state destabilization across the continent. Moving forward, the paper contends that Africa’s renewal, a “rebirth” akin to a spiritual transformation, requires a deliberate reconnection with its own historical legacy and epistemic roots. This involves transcending a human rights framework to embrace a more profound African conception of human dignity, fostering internal collaboration, and regenerating knowledge systems in education, technology, and culture. Ultimately, the path to a progressive Africa and a more equitable world lies not in linear catch-up but in a cyclical reclamation and modernization of indigenous African genius.